Pendampingan Pengemasan Produk Agar Lebih Menarik Untuk Menambah Daya Jual Pada Usaha Pabrik Tahu Pak Sugeng Sungai Hitam, Bengkulu Tengah: - Parolita, Inka; Gayatri , Ida Ayu Made Meytha (Jurnal Kewirausahaan dan Bisnis, 2024)
To meet consumer needs, the packaging of a food product is an important part of the food industry. Apart from being a container or wrapper for food, packaging also has a function to protect food. However, good packaging still prioritizes its function, namely to protect the product so that it is not only attractive in terms of appearance but also able to maintain the quality of the product. Tofu is one type of protein source food made from soybeans. Tofu is also a processed soybean product that has a fairly broad market segment. Until now, tofu does not have packaging that is suitable for packaging tofu, tofu traders usually sell their tofu using plastic bags. To be able to get the packaging according to the wishes of customers or the public to be more attractive or different from other tofu sellers, the packaging that is suitable for wrapping tofu is to use a box and also to make it more attractive it can be added with a logo so that the product is easily recognized by the public or customers. So using a method by providing direct counseling at the factory location by providing exposure to how to improve the quality of the packaging of tofu products produced. The results of this community service activity propose three aspects of solutions, namely paying attention to the quality of packaging related to the cleanliness of the tofu sold, maintaining the durability of the tofu sold with good packaging, adding product identity to the packaging to increase the selling value of the product.